Copeptin as a prognostic biomarker in acute myocardial infarction. (1st January 2019) - Lattuca, Benoit; Sy, Vuthy; Nguyen, Lee S.; Bernard, Maguy; Zeitouni, Michel; Overtchouk, Pavel; Yan, Yan; Hammoudi, Nadjib; Ceccaldi, Alexandre; Collet, Jean-Philippe; Kerneis, Mathieu; Diallo, Abdourahmane; et al.
Abstract: Background: Copeptin - the C-terminal section of vasopressin precursor - is a novel biomarker, that has been shown to be a useful prognostic factor in heart failure, ischemic stroke and in acute myocardial infarction (MI) but with restricted population and follow-up in ST-segment elevation MI (STEMI) setting. We evaluated in this study the hypothesis that copeptin measured on admission is an independent predictor of one-year all-cause mortality after a STEMI. Methods: Copeptin was measured immediately on arrival in the catheterization laboratory in a cohort of unselected STEMI patients and was compared to the peak of cardiac troponin I as a prognosis marker. One-year follow-up was performed. Results: We included 401 STEMI patients (77% of men, mean age 64 ± 14 years) treated by primary percutaneous coronary intervention. Copeptin on admission was significantly higher in patients who died during the one-year follow-up than in survivors (154.8 pmol/L; IQR [63.9–304.8] vs 30.3 pmol/L; IQR [10.8–93.5]); p < 0.0001). There was an increase in mortality at one year from the lowest to the highest quartile of copeptin. After Cox regression analysis, copeptin was an independent predictor of death at one year (adjHR 3.1, 95% CI [1.5–6.2], p = 0.001). When compared to the peak value of cardiac troponin I, copeptin measured on admission had a better prognostic value to predict one-year mortality (AUC of 0.74 vs 0.60, p = 0.022). Conclusion: Copeptin measured on admission is a reliable and independent prognostic biomarker of one-year mortality in acute myocardial infarction patients. Highlights: Largest evaluation of the prognostic value of copeptin in STEMI patients Higher copeptin level at admission in patients who died during the first year Copeptin: reliable and independent prognostic biomarker of one-year mortality Better predictive value of long-term survival of initial copeptin than troponin I peak